Chronic inflammatory periapical diseases: a Brazilian multicenter study of 10,381 cases and literature review - Aline Maria do COUTO; Daniela Pereira MEIRELLES; Alline Teixeira VALERIANO; Douglas Silva de ALMEIDA; Êmile de MORAES; Sandra Beatriz Chaves TARQUINIO; Aline Carvalho BATISTA; Elismauro Francisco de MENDONÇA; Nádia do Lago COSTA; Pollianna Muniz ALVES; Cassiano Francisco Weege NONAKA; Lucas Guimarães ABREU; et al. (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The aim of this study was to investigate the epidemiological and clinical characteristics of chronic inflammatory periapical diseases in different regions of Brazil and to compare with data from the literature. A multicenter study was carried out in four Brazilian referral centers in oral diagnosis. Histopathological records were reviewed, and all cases diagnosed microscopically as periapical granuloma, radicular cyst, and periapical abscess were included. Demographic and clinical data were collected. Descriptive statistics and Pearson's chi-square test were performed. A total of 10,381 cases of chronic inflammatory periapical diseases were found (13.8% of 74,931 archived specimens) over a period of 65 years. Radicular cysts were the most common lesion (59.9%). Women (56.1%) with a mean age of 37.01 years old (range 13 to 100 ± 14.42) and people of white skin color (59.2%) were the most affected individuals by chronic inflammatory periapical diseases. The lesions were generally asymptomatic (28.1%), located in the maxilla (60.1%), and posterior region (49.8%). The radicular cysts were larger when compared to periapical granulomas (p < 0.001). The disagreement between the clinical and histopathological diagnoses was higher when the final diagnosis was a periapical granuloma (p < 0.001). Chronic inflammatory periapical diseases continue to be common lesions affecting mainly adults. This should be a consequence of the burden of untreated caries in permanent teeth. Women are more affected and radicular cyst was the most common lesion.